Building New Paths in China - CEEC Academic & Research Cooperation: Initiatives in the Educational Cooperation of the University of Economics in Bratislava with the Zhejiang Province - Mattoš, Boris, 1977-
Akademická a výskumná kooperácia. Aktivity Ningbo, Zheijang provincie. Kooperácia Ekonomickej Univerzity v Bratislave s Ningbo, Zheijang provinciou.